Achieving ultra-high strength and ductility in a rare-earth-free magnesium alloy via precisely controlled secondary hot extrusion process with an extremely low extrusion speed - Wei Gao; Xin Wang; Yingjian Lin; Xiao Wang; Debao Liu; Xiaohao Sun (Journal of Magnesium and Alloys, 2024)
Magnesium (Mg) alloys, as the lightest structural metallic materials, hold significant potential for various applications in modern society. However, their limited strength and ductility have restricted their widespread use. Herein, a precisely controlled secondary hot extrusion (SHE) process with extremely low extrusion speed (a cross-head rate of 0.1 mm·min−1) was employed to achieve ultra-fine microstructure with an average grain size of 0.45 µm and uniform precipitation of nano-sized Mn-rich secondary phase in a rare-earth (RE)-free Mg-1.5Ag-0.2Mn-0.1Ca (wt.%) (MACM) alloy. Nano-sized Mn-rich secondary phase with an average particle size of 2.7 nm could inhibit the basal slip and result in the simultaneous activation of multiple slip systems, contributing to excellent ductility. Additionally, substantial elemental segregation occurred at the grain boundaries of the α-Mg phase in the SHEed Mg-Ag-Mn-Ca alloy after tensile deformation, providing significant solute drag pressure and Zener pressure. This phenomenon induces grain boundary segregation strengthening and activates non-basal slip. Consequently, the secondary hot extruded (SHEed) alloy exhibited an ultra-high ultimate tensile strength (UTS) of ∼422 MPa, a yield strength (YS) of ∼362 MPa, and an excellent elongation of 30.0%. Quantitative analysis of strengthening behavior in the SHEed MACM alloys revealed that the primary strengthening mechanism is grain refinement, with consideration given to the influences of Orowan strengthening and work hardening. This study provides a novel approach to synchronously ameliorate the strength and ductility in Mg-based materials for load-bearing applications.